2011
DOI: 10.12659/msm.881760
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of Zingiber corallinum Hance essential oil on drug-resistant bacteria and evaluation of its acute toxicity

Abstract: SummaryBackgroundThe excessive and irregular use of antibiotics could result in the generation and diffusion of drug-resistant bacteria. The aim of this study was to investigate the inhibitory effect of Zingiber corallinum Hance essential oil (ZCHO) on drug-resistant bacteria, especially on drug-resistant Acinetobacter baumannii.Material/MethodsSusceptibility testing was used to evaluate the effect of ZCHO on growth inhibition of drug-resistant bacteria by paper disk method. Mice orally administered with ZCHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Because all these positive interactions occur when components of essential oils are present, the results emphasize the potential of this class of phytochemicals for combinatorial therapy with antibiotics. In fact, this is supported by previous studies about the effects of essential oils and their constituents in the control of multidrug-resistant bacteria [21][22][23]. Kuroda et al demonstrated that farnesol at a sub-MIC inhibited S. aureus lipase (SAL) against 8 methicillin-susceptible and 31 methicillin-resistant S. aureus clinical isolates [24].…”
Section: Discussionmentioning
confidence: 77%
“…Because all these positive interactions occur when components of essential oils are present, the results emphasize the potential of this class of phytochemicals for combinatorial therapy with antibiotics. In fact, this is supported by previous studies about the effects of essential oils and their constituents in the control of multidrug-resistant bacteria [21][22][23]. Kuroda et al demonstrated that farnesol at a sub-MIC inhibited S. aureus lipase (SAL) against 8 methicillin-susceptible and 31 methicillin-resistant S. aureus clinical isolates [24].…”
Section: Discussionmentioning
confidence: 77%
“…MAC has been complete chemically defined and it was demonstrated that its antimicrobial activity could be principally attributed to terpinen-4-ol, the main active component [37,38,40,42,43,44]. Actually, terpinen-4-ol is the main bioactive antimicrobial component of essential oils derived from several aromatic plants [45,46,47]. On account of this, the interaction of terpinen-4-ol and the influenza virus haemagglutinin protein was predicted in silico to confirm the exact target and its active characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Our daily oral gavage doses were 8nL/g and 0.1nL/g diluted in purified water. These doses represent, respectively, 0.73% and 0.09% of the TP-4-ol Lethal dose (Yang et al 2011).…”
Section: Terpinen-4-ol Treatmentmentioning
confidence: 99%